School’s contribution to prevention of earthquakes - Drakoulakou, Georgia (Open Schools Journal for Open Science, 2018)
Greece is a highly seismogenic country. To be more specific, it is the 6th most seismically active country worldwide, as well as the very most earthquake-prone country in Europe. Undoubtedly, earthquakes is a natural phenomenon that people can’t prevent, or forecast. What we can do, is take appropriate measures in order to be shielded against this phenomenon. We should try to be informed enough and be active to protect ourselves. Prevention is the key word to this venture. And what can school do to make a difference? Of course, educate us the best way possible and care not only for our academic knowledge, but also for the growing of abilities, skills and qualifications that will contribute in our adaptation to the constant social changes, and will help us develop characteristics that will be proven useful in our future. After all we, students, are the future citizens of our world, and the only way to make it it is to be gifted enough.